Residents' awareness and support of tourism for strategic management purposes in Mahikeng - Litheko, A.M. (North-West University (South Africa), 2015)
Tourism is recognised as a means of boosting the national and regional economy. Increasingly destinations, and specifically cities, are turning to tourism as an important element in their economic portfolio. The Provincial Government of the North West province in South Africa considers tourism as an important sector that can contribute towards the economic growth, and for achieving broader social goals. One of the challenges tourism is facing is that governments and other role players do not always provide sufficient investment for the potential development of tourism and this then results in only marginal resources being assigned to tourism as an economic sector. Achieving competitive advantage in times of rapid change requires tourism to gather information and develop a clear understanding of the direction in developing tourism and its implications for a particular destination. Since tourism is intertwined with other economic sectors, tourism trends should ideally not be considered in isolation from the key drivers that shape South Africa's economic future. The main purpose of the study was establishing residents' (1) awareness and their (2) propensity to support tourism in Mahikeng. The reason for this is that a resident of a particular region or city forms a key factor contributing towards the development of a lucrative and prosperous tourism industry. This has enabled the researcher to gather insights and reasonable findings with regard to the level of residents' awareness and their likeliness to support tourism in Mahikeng. Consumer information, such as residents' awareness and support for tourism, is indispensable for strategic management purposes and contributes towards sustainable tourism development in Mahikeng. A total number of 365 questionnaires were distributed among residents of which 303 were completed and used. Questionnaires were distributed at residents' residential places and selected public areas. Data retrieved from the questionnaire were used and captured in the form of figures and tables. The main variables in this study were gender, age group, marital status, level of employment, occupational status, number of years residing in Mahikeng, and the number of times residents have visited tourism attractions in Mahikeng for the last 2 years. The result obtained can contribute towards the strategic planning and management of the North West Parks and Tourism Board (NWP&TB) and also towards stakeholders formulating strategies to grow and develop tourism in Mahikeng. Suggestions from the respondents were that those responsible for destination marketing should increase marketing efforts with the objective of raising the level of awareness amongst residents as that will prompt more support for tourism facilities. The development of sustainable tourism is difficult without the support and participation of local residents. Thus, the support of residents is a critical factor for ongoing development.
MCom (Management), North-West University, Mafikeng Campus, 2015
Keywords: Strategic management; Domestic tourism; Residents; Provincial government; Destination Marketing Organisation; Consumers